Influence Discipline and Motivation Work on Employee Performance ( Study Case of PT Employees . Slara Prime Commerce ) - Al Rangga, Muhammad Rafie; Candra, Ade (Universitas Pamulang, 2024)
Source reliable power​ is something that is needed in the era of globalization . Every organization company always expect source Power capable human​ Work in a way effective and efficient to achieve goals company can achieved . Study This carried out at PT Salara Niaga Prima. Retrieval technique sample done in a way random without notice starta in population . Data collection uses​ questionnaire closed . Analysis techniques used​ includes : validity test , reliability test , analysis regression multiple , coefficient correlation . Partial test results discipline Work influential positive to performance employees and motivation Work influential to performance employee . Whereas in a way simultaneous discipline work and motivation Work influential to performance employee .